Kepemimpinan Empatik dan Kesehatan Mental Karyawan dalam Mewujudkan Good Corporate Governance (GCG) di Perusahaan Industri di Indonesia - Jopinus Saragih; Hendri Mayanta; Joel Fernando Sirait (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This study aims to analyze the role of empathetic leadership and employees’ mental health in realizing Good Corporate Governance (GCG) in industrial companies in Indonesia. In the context of high job demands in the industry and the challenges of globalization and the Industrial Revolution 4.0, productivity needs to be balanced with good governance that prioritizes employee well-being. Using a quantitative approach with an explanatory survey method, the research involved 250 permanent employees from 10 industrial companies in West Java, East Java, and Banten. The variables were measured using scales for Empathetic Leadership, Employees’ Mental Health, and GCG Implementation, with data analysis including validity and reliability tests, multiple regression, path analysis, and the Sobel test to examine mediation effects. The findings show that empathetic leadership is at a high level (mean = 3.85), employees’ mental health is at a moderate level (mean = 3.45), and GCG implementation is at a moderate-to-high level (mean = 3.60). Empathetic leadership has a positive and significant effect on employees’ mental health (coefficient = 0.542; p < 0.001) and also a positive and significant effect on GCG implementation (coefficient = 0.321; p < 0.001). Employees’ mental health further shows a positive and significant influence on GCG implementation (coefficient = 0.487; p < 0.001). In addition, employees’ mental health partially mediates the relationship between empathetic leadership and GCG implementation (mediation effect = 0.264; p < 0.001). These results highlight the importance of a more holistic GCG approach that considers human and psychological factors affecting employees.